Safe dissemination of germplasm resources of banana - Thomas, John; Massart, Sébastien; Houwe, Ines van den; Roux, Nicolas Stephan M.; Crew, Kathy (Burleigh Dodds Science Publishing Limited, 2020)
This chapter focuses on key issues of the safe dissemination of banana germplasm, including germplasm conservation (field, in vitro and cryopreservation), seed and DNA banking, virus indexing and germplasm health, regulations on germplasm transfer and future trends in germplasm research.